Pengaruh Insentif Pajak, Sanksi Pajak, dan Modernisasi Administrasi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi UMKM di Kota Denpasar: Sosialisasi Perpajakan sebagai Variabel Moderasi - Ni Putu Pradnya Sugiantari Putri; Ni Putu Budiadnyani; Gine Das Prena; Putu Sri Arta Jaya Kusuma (Jurnal Akuntansi dan Pajak, 2025)
The MSME sector plays a crucial role in Indonesia's economy, contributing more than 90% of employment and 60% of GDP. However, the contribution of MSMEs to tax revenue remains suboptimal. Various challenges, such as innovation, technology, digital literacy, productivity, legality, financing, marketing, as well as training and facilities, significantly impact MSME tax compliance. This study aims to examine the influence of tax incentives, tax sanctions, and tax administration modernization on the tax compliance of individual MSME taxpayers in Denpasar, with tax socialization as a moderating variable. This quantitative research utilizes primary data collected through questionnaires measured using a Likert Scale. A total of 106 respondents were selected based on predetermined purposive sampling criteria. The study employs PLS-SEM analysis processed using SmartPLS version 4 software. The findings indicate that tax incentives and tax sanctions have a positive and significant effect on individual MSME taxpayers' compliance, while tax administration modernization has no significant effect. Furthermore, tax socialization does not moderate the relationships between tax incentives, tax sanctions, and tax administration modernization with taxpayer compliance. These results suggest that effective tax policies should incorporate more impactful strategies for socialization and implementation.